Advance in Digital Signal, Image and Video Processing - Falkowski-Gilski, Przemysław; Uhl, Tadeus; Łubniewski, Zbigniew (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint discussed Coding and compression; Content storing and management; Electronic media; Internet technology; Image and video signals; Multimedia processing; Quality of experience (QoE); Quality of service (QoS); Signal processing; Streaming services; Subjective and objective metrics; User experience (UX).